A distinct immunogenic region of glutamic acid decarboxylase 65 is naturally processed and presented by human islet cells to cytotoxic CD8 T cells. (January 2015) - Knight, R. R.; Dolton, G.; Kronenberg‐Versteeg, D.; Eichmann, M.; Zhao, M.; Huang, G. C.; Beck, K.; Cole, D. K.; Sewell, A. K.; Skowera, A.; Peakman, M.
Summary CD8 T cells specific for islet autoantigens are major effectors of β cell damage in type 1 diabetes, and measurement of their number and functional characteristics in blood represent potentially important disease biomarkers. CD8 T cell reactivity against glutamic acid decarboxylase 65 (GAD65) in HLA‐A*0201 subjects has been reported to focus on an immunogenic region 114–123 (VMNILLQYVV), with studies demonstrating both 114–123 and 114–122 epitopes being targeted. However, the fine specificity of this response is unclear and the key question as to which epitope(s) β cells naturally process and present and, therefore, the pathogenic potential of CD8 T cells with different specificities within this region has not been addressed. We generated human leucocyte antigen (HLA)‐A*0201‐restricted CD8 T cell clones recognizing either 114–122 alone or both 114–122 and 114–123. Both clone types show potent and comparable effector functions (cytokine and chemokine secretion) and killing of indicator target cells externally pulsed with cognate peptide. However, only clones recognizing 114–123 kill target cells transfected with HLA‐A*0201 and GAD2 and HLA‐A*0201+ human islet cells. We conclude that the endogenous pathway of antigen processing by HLA‐A*0201‐expressing cells generates GAD65114–123 as the predominant epitope in this region. These studies highlight the importance of understanding β cell epitope presentation in the design of immune monitoring for potentially pathogenic CD8 T cells.